Effects of shading, fertilization, and irrigation on floral display and honey yield in Agastache rugosa in controlled pot culture - Park, Ji-Min; Kim, Young-Ki; Kim, Hyun-Jun; Na, Sung-Joon (Frontiers in Plant Science, 2025)
Sustainable cultivation of Agastache rugosa requires quantitative guidance on how to balance ornamental floral display with nectar-mediated honey production under realistic limitations in light, nutrients, and water. Although this species is widely recognized as both an ornamental and melliferous plant, integrated management strategies that jointly optimize floral traits and honey yield under combined abiotic treatments remain poorly defined. This study aimed to clarify how shading, fertilization, and irrigation interact to shape growth, flowering, nectar traits, and estimated honey yield in A. rugosa, and to identify cultivation combinations that simultaneously support landscape quality and nectar provision. A three-factor, three-level factorial experiment was conducted in a randomized split-plot design with shading at 0, 35, and 55%, fertilization with N:P:K 20:20:20 at 0, 1, and 3 g/L, and irrigation at 2-, 4-, and 6-day intervals. Measured response variables included plant height, number of inflorescences per plant, inflorescence length, number of flowers per inflorescence, total flower number per plant, nectar volume per flower, and free sugar content per volume. Estimated honey yield per plant was calculated from nectar sugar content and flower number using a standard conversion approach. Fertilization and irrigation produced the largest increases in plant size, floral output, and estimated honey yield across shading levels, whereas nectar volume and sugar concentration were numerically stable and showed no consistent treatment response. The highest estimated honey yield, 0.7722 g/plant, occurred under 35% shading with 1 g/L fertilization and 2-day irrigation, where moderate shading and frequent watering enhanced floral display without diluting nectar sugar content. Together, these results indicate that moderate resource inputs can decouple floral architecture from nectar quality, enabling dual-purpose management of A. rugosa as an ornamental and melliferous crop in climate-adaptive production systems.